The Supply Chain Management in Financial Institution for Increasing the Productivity and Community Income in Pakraman Village, Bali - Putu Dyatmikawati; Ni Made Ruastiti (International Journal of Supply Chain Management, 2020)
Abstract- This study aims to determine and understand village financial institutions about community-owned loan businesses that are managed based on adat in the Pakraman village of Bali. The method used in the study is a qualitative method that is supported by quantitative methods. To complete and support the data, it is done by studying literature, interviewing, observing, documenting, and studying literature. The results showed that the existence of the Village Financial Institution in the development of the Pakraman village in Bali has been able to uncover the increase in operations in mobilizing community funds into productive funds to increase community income, support the physical development of the village (Balinese temple) and spiritual life in order to achieve peace in rural communities in Bali.